2016
DOI: 10.14742/ajet.3068
|View full text |Cite
|
Sign up to set email alerts
|

Lecture-recording technology in higher education: Exploring lecturer and student views across the disciplines

Abstract: This paper presents findings of an institutional case study investigating how students and lecturers experienced a new opt-out, fully integrated lecture-recording system which enabled audio and presentation screen capture. The study's focus is on how 'traditional' students (generally characterised as young, enrolled full-time and attending classes on campus) engaged with lecture-recording and how lecturers' experiences with, and attitudes towards, lecture-recording differed depending on their discipline. Stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…Kelly et al (2009) examined the use of pre-recorded instructional videos by undergraduate nursing students and found that students reported increased motivation for learning, and increased perception of readiness for practice. Dona et al (2017) studied the use of unscripted video lecture recordings in one institution. The authors found that 71% of the students who completed their survey perceived the inclusion of recorded lectures as a good supplemental learning tool.…”
Section: Live Lecture Recordingmentioning
confidence: 99%
“…Kelly et al (2009) examined the use of pre-recorded instructional videos by undergraduate nursing students and found that students reported increased motivation for learning, and increased perception of readiness for practice. Dona et al (2017) studied the use of unscripted video lecture recordings in one institution. The authors found that 71% of the students who completed their survey perceived the inclusion of recorded lectures as a good supplemental learning tool.…”
Section: Live Lecture Recordingmentioning
confidence: 99%
“…Works by Lokuge Dona, Gregory, & Pechenkina are devoted to studying this methodical aspect. In one of the articles they regard the question of traditional system effectiveness to record lectures and suggest taking the discipline specifics and even approaches to teaching into consideration (Lokuge Dona, Gregory, & Pechenkina, 2017).…”
Section: 5mentioning
confidence: 99%
“…Ongoing evaluation was needed not only to justify any further investment but to understand whether the new university policy had either encouraged staff uptake or bolstered resistance (Woodley et al, 2013). It was also important to determine if the requirements of different disciplines, compounded by the varying preferences of lecturers, were being met by a universal policy or if this was inculcating a "one-size-fits-all model of lecturing" (Dona, et al, 2016). Realist evaluation was an appropriate approach in this instance because there was ad hoc usage of the system at department level, that anecdotally seemed to work for some, but real evidence of what was working (or not), for whom, in which circumstances and why still needed to be understood.…”
Section: A Realist Evaluation Framework Tailored For Complex Learningmentioning
confidence: 99%